Impact of Process Optimization and Quality Improvement Measures on Neonatal Feeding Outcomes at an All-Referral Neonatal Intensive Care Unit. (July 2016) - Jadcherla, Sudarshan R.; Dail, James; Malkar, Manish B.; McClead, Richard; Kelleher, Kelly; Nelin, Leif
Aim: We hypothesized that the implementation of a feeding quality improvement (QI) program among premature neonates accelerates feeding milestones, safely lowering hospital length of stay (LOS) compared with the baseline period. Methods: Baseline data were collected for 15 months (N = 92) prior to initiating the program, which involved development and implementation of a standardized feeding strategy in eligible premature neonates. Process optimization, implementation of feeding strategy, monitoring compliance, multidisciplinary feeding rounds, and continuous education strategies were employed. The main outcomes included the ability and duration to reach enteral feeds–120 (mL/kg/d), oral feeds–120 (mL/kg/d), and ad lib oral feeding. Balancing measures included growth velocities, comorbidities, and LOS. Results: Comparing baseline versus feeding program (N = 92) groups, respectively, the feeding program improved the number of infants receiving trophic feeds (34% vs 80%, P < .002), trophic feeding duration (14.8 ± 10.3 days vs 7.6 ± 8.1 days, P < .0001), time to enteral feeds–120 (16.3 ± 15.4 days vs 11.4 ± 10.4 days, P < .04), time from oral feeding onset to oral feeds–120 (13.2 ± 16.7 days vs 19.5 ± 15.3 days, P < .0001), time from oral feeds–120 to ad lib feeds at discharge (22.4 ± 27.2 days vs 18.6 ± 21.3 days, P < .01), weight velocity (24 ± 6 g/d vs 27 ± 11 g/d, P < .03), and LOS (104.2 ± 51.8 vs 89.3 ± 46.0, P = .02). Mortality, readmissions within 30 days, and comorbidities were similar. Conclusions: Process optimization and the implementation of a standardized feeding strategy minimize practice variability, accelerating the attainment of enteral and oral feeding milestones and decreasing LOS without increasing adverse morbidities.